First record of Probstmayria tapiri (Nematoda: Atractidae) in Tapyirus bairdii (Gill, 1865) from the Chiapas Sierra Madre, Mexico. - Güiris Andrade, Darío M.; Rojas Hernández, Nidia M.; Berovides Álvarez, Vicente; Cruz Aldán, Epigmenio; Chávez Hernández, Carlos; Moguel Acuña, Jorge A.; Pérez Escobar, María E.; Palacios Mendoza, M. Gabriela (Instituto de Ecología, A.C., 2009)
This is a first record of Probstmayria tapiri in Mexico, was found in 60 (41.09%) fecal samples from Baird´s tapir (Tapirus bairdii) in the Biosphera Reserves La Sepultura and El Triunfo in the Sierra Madre de Chiapas, Mexico. Morphological characteristics of small nematode spindle-shaped forms truncated anteriorly and with a long, gradually attenuated, acutely pointed tail. Mouth with tree lips, pharynx elongated, aesophagus with tree portions: Anterior portion, long and slender, posterior portion, shorter, and pyriform portion, with a bulb. The excretory pore is situated near oesophagi bulb and ventral surface of the body. Vulva of female at about the middle of the body. Spicules assymetrical and curved. On the ventral surface of the tail there are nine small postanal papillae. These results allow us to extend their geographic distribution of nematode to Central America and another species of Tapir’s (T. bairdii). Finally we emphasized that the environmental conditions of La Sierra Madre de Chiapas, are optimal for the biological development of this nematode from tapirs of Central and South America.